The Stable Gastric Pentadecapeptide BPC 157 Pleiotropic Beneficial Activity and Its Possible Relations with Neurotransmitter Activity - Predrag Sikiric; Alenka Boban Blagaic; Sanja Strbe; Lidija Beketic Oreskovic; Ivana Oreskovic; Suncana Sikiric; Mario Staresinic; Marko Sever; Antonio Kokot; Ivana Jurjevic; Danijel Matek; Luka Coric; et al. (MDPI AG, 2024)
We highlight the particular aspects of the stable gastric pentadecapeptide BPC 157 pleiotropic beneficial activity (not destroyed in human gastric juice, native and stable in human gastric juice, as a cytoprotection mediator holds a response specifically related to preventing or recovering damage as such) and its possible relations with neurotransmitter activity. We attempt to resolve the shortage of the pleiotropic beneficial effects of BPC 157, given the general standard neurotransmitter criteria, in classic terms. We substitute the lack of direct conclusive evidence (i.e., production within the neuron or present in it as a precursor molecule, released eliciting a response on the receptor on the target cells on neurons and being removed from the site of action once its signaling role is complete). This can be a network of interconnected evidence, previously envisaged in the implementation of the cytoprotection effects, consistent beneficial particular evidence that BPC 157 therapy counteracts dopamine, serotonin, glutamate, GABA, adrenalin/noradrenalin, acetylcholine, and NO-system disturbances. This specifically includes counteraction of those disturbances related to their receptors, both blockade and over-activity, destruction, depletion, tolerance, sensitization, and channel disturbances counteraction. Likewise, BPC 157 activates particular receptors (i.e., VGEF and growth hormone). Furthermore, close BPC 157/NO-system relations with the gasotransmitters crossing the cell membrane and acting directly on molecules inside the cell may envisage particular interactions with receptors on the plasma membrane of their target cells. Finally, there is nerve-muscle relation in various muscle disturbance counteractions, and nerve-nerve relation in various encephalopathies counteraction, which is also exemplified specifically by the BPC 157 therapy application.